The Effect of Xenon on the Activity of Glycogen Synthase Kinase-Зβ in the Perifocal Zone of Ischemic Cerebral Infarction (Experimental Study) - A. V. Ershov; I. A. Krukov; V. V. Antonova; A. A. Baeva (Общая реаниматология, 2023)
Aim of the study. To determine the effects of xenon exposure at a dose of 0.5 MAC of different duration on the content and enzyme-inactivating phosphorylation of the glycogen synthase kinase-3β (GSK3β) in the perifocal zone of ischemic cerebral infarction in an experimental setting.Materials and methods. The Long method was used for modelling brain ischemia/reperfusion in 39 rats weighing 300-350 g. Study group animals was exposed to xenon at a dose of 0.5 MAC during 30, 60 and 120 minutes whereas control group animals received an oxygen-air mixture. Sham-operated animals served as a comparison group. The levels of GSK3β and phospho-GSK3β in brain homogenates were determined by blotting using specific antibodies.Results. In ischemic stroke model, the content of GSK3β did not significantly change in control animals compared to comparison group. However, control group animals exhibited significant (2.7-fold, P<0.001) decrease in the content of its phospho-GSK3β in the perifocal zone of ischemic cerebral infarction. Inhalation of 0.5 MAC xenon during 30 minutes did not lead to an increase in phosphorylation of the GSK3β enzyme (P=0.9), however, 60 and 120 minutes of 0.5 MAC xenon exposures resulted in the increase in phosphorylated form of the enzyme by a factor of 2.1 (P=0.005) and 2.3 (P=0.001), respectively, compared to the control group.Conclusion. The results reveal a possible molecular mechanism (i. e., execution of neuroprotective and anti-inflammatory effects of xenon due to GSK-Зβ inactivation) and show the prospects for using 60 and 120 minutes of 0.5 MAC xenon exposures in ischemic brain damage after a stroke, traumatic brain injury and other brain lesions.